2005
DOI: 10.1177/0974909820050204
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Application of Prostaglandin E1 on Orthodontic Tooth Movement - A Clinical Trial

Abstract: Assoc iate Pro fesso r, Dept. of O rth odo nti cs a nd De ntofac ia l O rth o pedi cs, SDM De nt a l In stitut e, Dh a rwad, Ka rn ata ka, In di a. K. M. Ke luskar MDS, Professor, He ad, De pt. of Orth odo nti cs a nd De ntofac ial O rthopedi cs, KLE De nta l Institute, Be lga um , Ka rn a tak a, In dia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Corticosteroid hormones, vitamin D3, parathyroid hormone, and thyroxin have all been shown to increase tooth movement in animal studies . In human trials investigating the application of prostaglandins on tooth movement, the results have suggested a possible acceleration . Therefore, drugs blocking their action, such as aspirin and NSAID's could slow orthodontic tooth movement as demonstrated in additional animal studies .…”
Section: Non‐surgical Methodsmentioning
confidence: 96%
“…Corticosteroid hormones, vitamin D3, parathyroid hormone, and thyroxin have all been shown to increase tooth movement in animal studies . In human trials investigating the application of prostaglandins on tooth movement, the results have suggested a possible acceleration . Therefore, drugs blocking their action, such as aspirin and NSAID's could slow orthodontic tooth movement as demonstrated in additional animal studies .…”
Section: Non‐surgical Methodsmentioning
confidence: 96%
“…Another prostaglandin that has been reported to speed up orthodontic tooth movement is Prostaglandin E 1 (PGE 1 ). Prostaglandin E 1 (PGE 1 ) has also been seen to be induced by mechanical stress and cause bone remodelling, Patil and his co-workers had shown that even minimal amounts of PGE 1 injection had significant increase in tooth movement [9]. Due to the hyperalgesia that accompanies with the local injection of PGE 1, an analogue of it which is misoprostol was tried out.…”
Section: Pharmacological Methodsmentioning
confidence: 99%
“…[40] and Anand et al . [44] demonstrated increased rate of orthodontic tooth movement with exogenous injections of PGE2 [Figures 2 and 3]. Studies indicate that Prostaglandins increase the number of osteoclasts as well as stimulate osteoblastic cell differentiation and new bone formation.…”
Section: Role Of Prostaglandins In Mediating Otmmentioning
confidence: 99%